Beer, brewing, and business history. Issue 5 (3rd July 2016) - Cabras, Ignazio; Higgins, David M.
Abstract: This editorial introduces the eight articles in the special issue on 'Beer, brewing and business history'. Following the BEERONOMICS conference held at the University of York, 2013, and the subsequent approval of the editorial board of Business History, we received many submissions discussing beer, brewing, and their importance to business history (broadly defined). In this editorial we provide a brief overview of the historical development of beer and brewing; explain the appeal to business historians of the principal themes which have emerged in the historiography of this industry, and provide a short introduction to the articles accepted for publication in this special issue.